Aspek Ideologis dan Pendidikan Religiusitas dalam Novel-Novel Bertema Islam Karya Penulis Perempuan Muslim Indonesia Era Pascareformasi - Rumtini, Rumtini; Susanto, Dwi (Humanis; Vol 29 No 2 (2025)DO - 10.24843/JH.2025.v29.i02.p09, 2025)
One significant trent in post-reform Indonesian literature is the emergence of Islamic-themed novels, notably those by Habiburrahman El Shirazy, Abidah El Khalieqy, and Helvy Tianna Rosa. This study aims to: 1). examine the educational values; 2). Analyze the ideological aspects presented in selected novels. Using qualitative method, the research involved close reading of Islamic-themed works by Indonesian women writer, sample selection, and thematic analysis. Findings indicate that Perempuan Berkalung Sorban convey educational values throught its critique of gender subordination within traditional pesantren culture, highlighting women’s struggle for right. Meanwhile, Ketika Mas Gagah Pergi promotes adherence to Islamic Sharia as as comprehensive lifestyle, including political dimentions. Ideologically, Perempuan Berkalung Sorban reflects a feminist spirit that acknowledges gender distinctions, while Ketika Mas Gagah Pergi aligns with Indonesia’s hijra movement and post-Islamist discourse. These novels thus serve as cultural texts articulating educational and ideological narratives within contemporary Islamic literature.